Nonfamilial, MPL S505N-Mutated Essential Thrombocythaemia - Ruth Morrell; Stephen E. Langabeer; Liam Smyth; Meegahage Perera; Gerard Crotty (Case Reports in Hematology)
Mutations of MPL are present in a significant proportion of patients with the myeloproliferative neoplasms (MPN), primary myelofibrosis (PMF), and essential thrombocythaemia (ET). The most frequent of these mutations, W515L and W515K, occur in exon 10 of MPL, which encodes the receptor for thrombopoietin. Another exon 10 mutation, MPL S505N, has been shown to be a founder mutation in several pedigrees with familial thrombocythaemia where it is associated with a high thrombotic risk, splenomegaly and progression to bone marrow fibrosis. Rare cases of sporadic, nonfamilial, MPL S505N MPN have been documented, but the presenting laboratory and clinical features have not been described in detail. The diagnosis and clinical course of a case of MPL S505N-positive MPN are presented with diagnostic features and treatment response resembling typical ET but with evidence of increasing bone marrow fibrosis. Further MPN cases possessing this genotype require reporting in order to ascertain whether any particular morphological or clinical features, if present, determine clinical course and aid the refinement of therapeutic options.